An interview with Holmes Rolston III - Chinese - Rolston, Holmes, 1932-2025, interviewee; Libenson, Sam, interviewer; Wong, Justin, interviewer; Ma, Chenghui, translator (Colorado State University. Libraries, 2022)
Holmes Rolston is interviewed by Sam Libenson and Justin Wong. Environmental ethics is about appropriate caring and respect for wonderland Earth and its inhabitants, each flourishing according to its own nature. Earth is a marvelously distinct planet with the richness of life that has evolved here ‒ a wonderland. Life contains information, encoded in genes, about how to construct and maintain an ongoing form of life. This is more marvelous than elsewhere in the universe so far as we know. Part of the meaning of life can be found in science, but not the deeper meanings in religion. We ought to use technology save half-Earth.
Chinese translation done by Chenghui Ma, Heilongjiang University, China - Associate Professor.
The whole 2022 annual issue is on Philosophy and the Environment, with contributed articles. The Harvard Review of Philosophy each year conducts interviews with philosophers considered groundbreaking and on the leading edge of philosophy. Rolston is one of three interviewed here. Two others are J. Baird Callicott and Peter Singer.
Keywords: Rolston, Holmes, 1932-2025 -- Interviews; environmental ethics; wonderland Earth; genetic coding; science; religion; technology; half-Earth